Islamic Epistemology and Its Implications for Contemporary Curriculum Design - Saro’i, Mohammad; Munir , Munir (Civiliza Publishing, Indonesia., 2025)
Contemporary educational curricula in many Muslim countries, including Indonesia, are still dominated by a secular paradigm that separates knowledge from spiritual values, thus creating a disorientation in educational objectives. This study aims to examine Islamic epistemology as an alternative foundation in designing an integral curriculum oriented towards the formation of a perfect human being. Using a qualitative approach through literature review, this study analyzes the works of classical and contemporary Islamic figures as well as relevant modern educational theories. The results show that Islamic epistemology views knowledge as a unity derived from revelation, reason, and experience, thus providing a transformative direction in the formulation of educational objectives, curriculum content, learning methods, and evaluation. The conclusion of this study confirms that the application of Islamic epistemology in curriculum design can address the value crisis in modern education and reorient education towards the formation of knowledgeable and moral human beings. The contribution of this study lies in the presentation of the concept of a monotheistic value-based curriculum that can serve as a philosophical and practical basis for contemporary Islamic educational reform.